Remittance and Inflation Dynamics in Nepal: An Econometric Analysis - Joshi, Uttam Lal (International Research Journal of MMC, 2024)
This empirical study investigates the remittance and inflation dynamics in the present context of Nepal. Major objective of the study is to find out the impact of remittance on inflation in Nepal. It also aims to find out the relationship between CPI and the independent variables- remittance, exchange rate, money supply and population. Data were obtained from the published source of world bank from 1993 to 2022. Augmented Dickey-Fuller unit root test was implied to test the stationary situation of the variables to remove the problem of spurious regression. After confirming some variables were integrated in I (0) and some are in I (1) order, ARDL model was applied to find out co-integration of the variables for long run relationship. Error corrections model was used after ARDL model that helps to show the speed of adjustment towards long-run equilibrium. Results show remittance and inflation are co-integrated and the coefficient of error correction term was negative and significant which indicates the long-run relationship. So remittance from foreign sectors should be used not only in consumption sectors that promotes inflation but it should be used in productive sectors too. This study will be helpful to policymakers whether remittance is causing inflation in the country.